The Rome Call and The Dynamics of Institutionalizing Ethics in Artificial Intelligence Governance - Pakpahan, Saiman; Ermansyah, Bambang Putra (Journal of Governance, 2025)
This article examines the institutionalization of ethical norms in the governance of artificial intelligence (AI), focusing on the Rome Call for AI Ethics as a global initiative. The study addresses the ethical challenges posed by AI, including algorithmic bias, privacy violations, and social inequality. Using constructivism and the "norm life cycle" framework, it analyzes the emergence, diffusion, and internalization of ethical principles such as transparency, inclusion, and accountability. Findings highlight the critical roles of international organizations, private corporations, and civil society in advocating for these norms. However, challenges such as capacity disparities between nations and resistance from key actors persist. The study underscores the importance of cross-sectoral collaboration and localized approaches to ensure equitable adoption of AI ethics. By offering insights into global norm institutionalization, this research contributes to the discourse on creating responsible and sustainable AI governance frameworks that prioritize humanity's collective welfare.